Labor force participation of married woman in Russia - Salim Turdaliev (Charles University in Prague, Institute of Economic Studies (IES), 2020)
Women make up a little over half the world's population, but their contribution to the labor force is far below its potential, with serious macroeconomic consequences. Despite a recent progress, labor markets across the globe remain divided along gender lines, and female LFP remains lower than the participation of their male counterparts. This paper assesses the determinants of labor force participation of married woman in Russia, using data obtained from Russian Longitudinal Monitoring Survey (RLMS). The study employs two-step Heckman selection model whose major function is to give unbiased estimators of the parameters of the wage function, which could serve to estimate parameters of a structural equation of participation. Two types of proxies (the presence of children and household income characteristics) that affect the married female's opportunity cost of working but do not generate sample selection mechanisms are used in order to overcome the identification problem in the first-stage wage equation. The estimated semi-elasticity of married female participation to wage is equal to 0.24. The findings of the study also indicate that such factors as gender, age, the presence of dependent children, educational attainment, location and the religious affiliation are the significant determinants of the LFP. The income of the other household members, and race of the respondent, on the other hand, proved to be insignificant determinants of labor supply. As a result, the empirical evidence provided by this project can be useful in future assessments of current social security and employment policies implemented in transition economies.
Keywords: J21; J22; J31; 330; female labour supply; economic transition; Russian labour market